The Transmutated Self: Peeping into Jaycee Duggard‟s Ab-Humanity in A Stolen Life - Boruah, Uttam; Bharadwaj, Shrestha (International Journal of Psychosocial Rehabilitation, 2020)
She was a little girl forced into a woman. With a raped body and a shattered existence, her mind, body and soul were torn down into nihility. Kidnapped at the age of 11, Jaycee Duggard was incarcerated by Philip Garrido for 13 years. Physically, mentally as well as sexually assaulted by Philip, Duggard’s identity as a human was invalidated, forcing her into emerging as an ‘ab-human’. She was just an object of male pervasive desires that reduced her existential consciousness and her notion of self. A reduced self, she had to suffer the ultimate crisis of her body that eventually determined her presence. The present paper tries to analyze the shattered self of Jaycee Duggard and the consummation of her identity as a human being. Her space of confinement, both physical and emotional, and her subaltern identity that aided in reducing her extant and individuality, will also be examined.